Large extracellular vesicles carry most of the tumour DNA circulating in prostate cancer patient plasma. Issue 1 (1st January 2018) - Vagner, Tatyana; Spinelli, Cristiana; Minciacchi, Valentina R.; Balaj, Leonora; Zandian, Mandana; Conley, Andrew; Zijlstra, Andries; Freeman, Michael R.; Demichelis, Francesca; De, Subhajyoti; Posadas, Edwin M.; Tanaka, Hisashi; et al.
ABSTRACT: Cancer-derived extracellular vesicles (EVs) are membrane-enclosed structures of highly variable size. EVs contain a myriad of substances (proteins, lipid, RNA, DNA) that provide a reservoir of circulating molecules, thus offering a good source of biomarkers. We demonstrate here that large EVs (L-EV) (large oncosomes) isolated from prostate cancer (PCa) cells and patient plasma are an EV population that is enriched in chromosomal DNA, including large fragments up to 2 million base pair long. While L-EVs and small EVs (S-EV) (exosomes) isolated from the same cells contained similar amounts of protein, the DNA was more abundant in L-EVs, despite S-EVs being more numerous. Consistent with in vitro observations, the abundance of DNA in L-EV obtained from PCa patient plasma was variable but frequently high. Conversely, negligible amounts of DNA were present in the S-EVs from the same patients. Controlled experimental conditions, with spike-ins of L-EVs and S-EVs from cancer cells in human plasma from healthy subjects, showed that circulating DNA is almost exclusively enclosed in L-EVs. Whole genome sequencing revealed that the DNA in L-EVs reflects genetic aberrations of the cell of origin, including copy number variations of genes frequently altered in metastatic PCa (i.e. MYC, AKT1, PTK2, KLF10 and PTEN ). These results demonstrate that L-EV-derived DNA reflects the genomic make-up of the tumour of origin. They also support the conclusion that L-EVs are the fraction of plasma EVs with DNA content that should be interrogated for tumour-derived genomic alterations.